POLARIZATION OF LOCAL COMMUNITY ORIENTATION TO THE DEVELOPMENT OF ECO-RURAL TOURISM IN KERINCI REGION, JAMBI PROVINCE, INDONESIA - Bonanza, Occy; Avenzora, Ricky; Malihah, Elly; Hermawan, Rachmad (Association of Indonesian Forestry and Environment Researchers and Technicians, 2024)
Rural areas are increasingly the focus of exploration by various stakeholders. However, local communities, as landowners in these regions, often do not reap the full benefits. This issue stems from their limited involvement in regional development and a lack of awareness about ongoing projects. Local communities play a crucial role in the success of rural development, and understanding their attitudes is vital.This study aimed to explore local community attitudes toward eco-rural tourism development in Kerinci Regency, Jambi Province. A closed-ended questionnaire, designed with a